Digitalisasi dan Kinerja ASN: Peran Keterlibatan Kepemimpinan Mediasi Kebijakan Pemerintah Daerah - Sri Kasnelly; Ahmad Luthfi; Shofia Amin; Zulfina Adriani; Dahmiri Dahmiri (Ekonomis: Journal of Economics and Business, 2026)
Digital government transformation requires civil servants to integrate technology, competence, infrastructure, and leadership. In district governments, local policy is often assumed to mediate these capabilities toward performance, yet evidence remains limited. This study examines the effects of technology adoption, digital competence, digital infrastructure, and leadership involvement on civil servant performance, with local government policy as a mediator. Dynamic Capability Theory is the main lens, supported by TAM/UTAUT, while Upper Echelon Theory is treated as a boundary condition because leadership is measured at the section/division-head level. An explanatory quantitative design was applied to 186 civil servants in Tanjung Jabung Barat Regency and analyzed using PLS-SEM. All four antecedents significantly improved performance (R² = 0.777), with leadership involvement as the strongest predictor. Local policy was predicted by the antecedents but neither affected performance nor mediated the relationships (direct-only nonmediation). District-level digital performance depends more on operational capabilities and middle-level leadership than on perceived formal regulation. The study extends DCT to local bureaucracy and directs policy toward implementation, system integration, and operational digital leadership.